Golden Gate International Exposition Grounds, Golden Gate Bridge and San Francisco-Oakland Bridge by Night, Oakland and Berkeley in Foreground, San Francisco in Background (Western Notion & Novelty Co.)
In its spectacular setting between the world's two largest bridges spanning San Francisco Bay, is the site of the 1939 International Exposition now being reclaimed on Yerba Buena shoals. The 400-acre site is larger than Chicago's Century of Progress. Oakland, the Eastbay Empire, lies in the foreground. In the left background lies San Francisco